RELATIONSHIP BETWEEN MANGROVE SEEDLING GROWTH, NUTRIENTS AND HEAVY METAL CONCENTRATIONS IN SOIL AT CAREY ISLAND, SELANGOR, MALAYSIA - M. Z., Rozainah; N. A., Affandi; M. T., Noraini (Malaysian Journal of Science, 2014)
A comparative study in the relationship between mangrove seedling growth and heavy metal concentrations in sediment was conducted at Carey Island, Malaysia. Two contrasting stations were chosen; natural habitat and reforestation site. Avicennia alba and Rhizophora apiculata were chosen as the test species. At the reforestation site, R. apiculata showed higher increments of stem height (1.74cm mth-1) compared to A. alba (1.28 cm mth-1), although both species produced 1 leaf per month. On the other hand, A. alba showed better increment of height (2.17 cm mth-1) and produced 2 leaves per month in the natural habitat. R. apiculata has very slow growth, at only 0.65 cm mth-1 and produced 1 leaf per month. Pearson correlation deducted that A. alba showed positive correlation in growth with Mg at the reforestation site, and with sulfate and chloride in natural habitat. At the reforestation site, R. apiculata showed positive correlation with Ca and Cu but did not record any significant correlation with those elements in the natural habitat. Keywords: Heavy metal, Straits of Malacca, mangrove, nutrients